ANALISIS INKONSISTENSI KEBIJAKAN PERTANAHAN DI KABUPATEN KEPULAUAN MERANTI TAHUN 2020 - Yoga Febryan Supardi; Isril " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Complete Systematic Land Registration is carried out to provide guarantee of legal certainty and legal protection of land rights. To ensuring legal certainty and legal protectionas well as program acceleration Complete Systematic Land Registration (PTSL), various rules have been published. After the community gets their own Land Certificate, it arises problems during the issuance of Presidential Instruction No. 5 of 2019 concerning Termination Granting new permits and improving primary natural forest governance and Peatlands. The emergence of rules related to the Indicative Map of Termination of GivingNew Permits (PIPPIB) have made it difficult for almost entirety areas categorized as a PIPPIB area such as the Meranti Islands Regency. People have land certificates, but can't do anything against the certificate because it cannot carry out various activities neither the property rights of their land. This research was conducted with dunn theory (1991). According to Dunn (1991),There are three forms or models of policy analysis, namely prospective models, models retrospectives and integrative models. A retrospective model is a policy analysis done to the consequences of a policy "after" a policy Implemented. This model is usually referred to as an evaluative model, because Many involve an evaluation approach to the impact of policy impacts is or has been implemented. According to Dunn Policy analysis can be focused into various levels. Three main focuses commonly selected in the analysis Social policy includes : 1. Definition of social problems 2. Policy implementation social 3. Consequences of social policy. Indicative Map Assignment Policy Termination of New Permissions(PIPPIB) this is a unilateral policy of the Central Government withoutcoordinate with local governments, by directly establishing determinationsIndicative Map of Termination of New Permits (PIPPIB) regardless of conditionsreal in the field. This is an inappropriate policy for local governments. The Central Government should look at the real conditions and coordinate points before establishing a policy of Indicative Map Determination of Deprecation of GivingNew Permit (PIPPIB). But the reality is that the central government is directlyset this policy. According to Law No. 23 of 2014 concerningLocal Government. Keywords: Analysis, Policy, Inconsistency